Prevalence and determinants of prehypertension among youth in Ghana - Dzokoto, Maxwell K.; Mensah, Benjamin T. (International Journal Of Community Medicine And Public Health, 2020)
Background: Recent studies showed an increased prevalence of prehypertension and alarming trend of prehypertension among the youth. This study was aimed at determining the prevalence of prehypertension and its determinants among male youth in Ghana. Methods: The study retrieved data from the 2014 Ghana Demographic and Health Survey (GDHS). For this study, the data related to men was used and those aged 15-24 years were extracted for the analysis. The sample which comprised of 1,363 respondents was analysed using descriptive statistics, simple and multiple logistic regressions. Multicollinearity test was also carried out using the variance inflation factor and tolerance to determine independents variables that were correlated. Crude and adjusted odds ratios were reported accordingly. Results: The overall prevalence of prehypertension was 5%. Among those who were pre-hypertensive, 4.1% were secondary school graduates and 2.6% were not sexually active in the last four weeks prior to the study. Similarly, 4.3% of those who were pre-hypertensive had their blood pressure taken in the morning. Occupation and region of residence played significant roles in prehypertension prevalence. Whilst arm circumference, sexual behaviours and smoking habit were significant predictors of prehypertension. Conclusions: Educational level, occupation, sexual behaviours such as having too many sexual partners, and smoking were significant predictors of prehypertension. This study suggests that education on the importance of regular blood pressure monitoring among the youth should be intensified. Also, education hinging on some of the negative effects of cultural shifts and transformations like sexual partners’ acquisition should be intensified.